2014
DOI: 10.1002/pchj.47
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in distractibility: An update and a model

Abstract: This paper reviews the current literature on individual differences in susceptibility to the effects of background sound on visual-verbal task performance. A large body of evidence suggests that individual differences in working memory capacity (WMC) underpin individual differences in susceptibility to auditory distraction in most tasks and contexts. Specifically, high WMC is associated with a more steadfast locus of attention (thus overruling the call for attention that background noise may evoke) and a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 169 publications
(192 reference statements)
9
44
0
Order By: Relevance
“…This explanation is in line with the predictions of the task‐engagement/distraction trade‐off model by Sörqvist and Rönnberg (). In dual‐task studies investigating auditory distraction under visual WM updating load, these authors and others observed that task‐irrelevant auditory stimuli caused less interference under high as compared to low visual WM updating load (San Miguel, Corral, & Escera, ; Sörqvist, Stenfelt, & Rönnberg, ).…”
Section: Discussionsupporting
confidence: 91%
“…This explanation is in line with the predictions of the task‐engagement/distraction trade‐off model by Sörqvist and Rönnberg (). In dual‐task studies investigating auditory distraction under visual WM updating load, these authors and others observed that task‐irrelevant auditory stimuli caused less interference under high as compared to low visual WM updating load (San Miguel, Corral, & Escera, ; Sörqvist, Stenfelt, & Rönnberg, ).…”
Section: Discussionsupporting
confidence: 91%
“…While enhanced negativity in the P1/N1 range under low WM load during SI fits well with the Efforts Model and task-engagement/distraction trade-off model [68,69], there is room for another interpretation. It is possible that when WM load increases, the task-irrelevant probes are processed less, while the task-relevant source message still receives the same amount of attention as it does under low WM load.…”
Section: Discussionmentioning
confidence: 61%
“…In this respect, one possibility is that, like with many abnormalities that co-vary with inferior WMC (Sörqvist & Rönnberg, 2014), the low WMC of high-schizotypy individuals underpins their greater susceptibility to distraction. This hypothesis is tested in the experiment reported here in two ways.…”
Section: Present Studymentioning
confidence: 99%